1998
DOI: 10.1300/j013v26n02_04
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Colon Cancer Coverage in Seven Women's Magazines

Abstract: Women's magazines are an important source of health information. To evaluate the relevancy of articles in these publications to known disease risks, seven women's magazines were reviewed to assess their coverage of colon cancer, the third leading cause of cancer mortality in U.S. women. Specifically, the amount of coverage devoted to colon cancer as well as the presentation of issues in the prevention, risks, treatment, diagnosis and genetics of colon cancer were recorded. Twenty articles were published on col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…First, most studies of cancer in the media where a comparative count is done find that breast cancer is over-reported compared to its incidence in the population , Dymock and Hill 1999, Gerlach et al 1997, Marino and Gerlach 1999, Sarna 1995, Saywell et al 2000 as it appeals to news editors for a variety of (largely sexist) reasons (Henderson and Kitzinger 1999, Lantz and Booth 1998, Lupton 1994. For this study, though, a further reason is that the first week of October has been designated`Breast Cancer Awareness Week' by various influential cancer organisations, meaning that there was increased coverage of charity fundraising events and book launches relating to breast cancer autobiographies (13 PWCs were reported as having written books about their cancer experience; 11 of these were women writing about their breast cancer).…”
Section: Methods and Samplementioning
confidence: 99%
“…First, most studies of cancer in the media where a comparative count is done find that breast cancer is over-reported compared to its incidence in the population , Dymock and Hill 1999, Gerlach et al 1997, Marino and Gerlach 1999, Sarna 1995, Saywell et al 2000 as it appeals to news editors for a variety of (largely sexist) reasons (Henderson and Kitzinger 1999, Lantz and Booth 1998, Lupton 1994. For this study, though, a further reason is that the first week of October has been designated`Breast Cancer Awareness Week' by various influential cancer organisations, meaning that there was increased coverage of charity fundraising events and book launches relating to breast cancer autobiographies (13 PWCs were reported as having written books about their cancer experience; 11 of these were women writing about their breast cancer).…”
Section: Methods and Samplementioning
confidence: 99%
“…The few studies that have examined the health-related content of magazines by the magazines' ethnic orientations have found some significant differences in the amount of health information directed at Black female and White female audiences. Gerlach et al found that coverage of colon cancer was greatly underrepresented in both White and Black women's magazines, compared to the risk the disease poses to women, but African American magazines contained many fewer articles on colon cancer than did White-oriented magazines [53]. Omonuwa reported more than four times as many advertisements for prescription and nonprescription drugs in White women's magazines as in those directed at Black women, without adjusting for the number of pages in the magazines [54].…”
Section: Introductionmentioning
confidence: 99%
“…Gerlach, Marino, Weed, & Hoffman-Goetz, 1997). Poorer media coverage of CC cancer may be due to limited public awareness and fewer advocacy groups (Friedman & Hoffman-Goetz, 2003;Hoffman-Goetz & Friedman, 2005).…”
Section: Discussionmentioning
confidence: 99%